1972
DOI: 10.1042/bj1300475
|View full text |Cite
|
Sign up to set email alerts
|

Role of light in the synthesis of nitrate reductase and nitrite reductase in rice seedlings

Abstract: 1. In rice seedlings synthesis of methyl viologen-nitrite reductase was stimulated by light, as was that of NADH-nitrate oxidoreductase (EC 1.6.6.1). A small residual effect of light on the synthesis of the enzymes persisted in the dark for a short time. 2. In etiolated seedlings exposed to light and nitrate, a lag period of 3h was necessary before enzyme synthesis commenced, whereas in green seedlings kept in the dark for 36h, synthesis of both the enzymes started as soon as light and nitrate were provided. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In comparison to the control grown in the Mg 2+ -present media, the contents of free amino acid and soluble protein Fig. 1 20.51% and 61.97%, respectively, while those of Ce 3+ -treated group grown in the Mg 2+ -deficient media were alleviated by 7.69% and 13.36%, and in the Mg 2+ -present media were increased by 5.13% and 38.03%, respectively. We also observe that deprivation of Mg 2+ inhibited chlorophyll formation of spinach significantly, and Ce 3+ treatment could promote chlorophyll formation, particularly grown in the Mg 2+ -deficient media.…”
Section: The Contents Of Free Amino Acid Chlorophyll and Soluble Prmentioning
confidence: 61%
See 1 more Smart Citation
“…In comparison to the control grown in the Mg 2+ -present media, the contents of free amino acid and soluble protein Fig. 1 20.51% and 61.97%, respectively, while those of Ce 3+ -treated group grown in the Mg 2+ -deficient media were alleviated by 7.69% and 13.36%, and in the Mg 2+ -present media were increased by 5.13% and 38.03%, respectively. We also observe that deprivation of Mg 2+ inhibited chlorophyll formation of spinach significantly, and Ce 3+ treatment could promote chlorophyll formation, particularly grown in the Mg 2+ -deficient media.…”
Section: The Contents Of Free Amino Acid Chlorophyll and Soluble Prmentioning
confidence: 61%
“…NiR activity was measured following the method of Sawhney and Naik [20]. The assay mixture in a final volume of 2 ml contained 100 μM phosphate buffer (pH 7.5), 1.0 μM NaNO 2 , 0.4 μM methylviologen, and 0.5 ml of enzyme extract.…”
Section: Assay Of Free Amino Acid and Soluble Protein Contentmentioning
confidence: 99%
“…This was the conclusion drawn from experiments using protein synthesis inhibitors to prevent the appearance of nitrite reductase activity in Lemna [12] and bean leaves [15]. However in similar experiments with maize [ll] and rice [13], chloramphenicol prevented the appearance of nitrite reductase activity and it was suggested that the protein was synthesisied on chloroplast ribosomes [l 11. Our attempts to demonstrate the synthesis of nitrite reductase by isolated chloroplasts from pea and wheat (I. S. Small and A. L. Phillips, unpublished) and by the coupled transcriptiontranslation of chloroplast DNA from pea and wheat (A. K. Huttly, unpublished) have been unsuccessful, further suggesting that synthesis occurs outside the chloroplasts in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Nitrate reductase activity was determined Invivo conditions (Sawhney and Naik, 1972). The enzyme was assayed colorimetrically by monitoring the amount of nitrite produced.…”
Section: Enzymes Of Nitrogen and Phosphorous Metabolismmentioning
confidence: 99%